Surface nano-crystallization and its effect on the microstructure evolution and mechanical properties of lightweight Fe–28Mn–8Al–1C steel subjected to supersonic fine particle bombardment - Yi Xiong; Wei Lv; Xiao-qin Zha; Yong Li; Ze-wei Luan; Tian-tian He; Kang-hao Shu; Feng-zhang Ren; Ge Zheng (Journal of Materials Research and Technology, 2023)
The surface nano-crystallization of lightweight Fe–28Mn–8Al–1C steel was achieved via the supersonic fine particle bombardment (SFPB) technique. The effects of impact time of SFPB and gas pressure on the surface morphology, microstructure, and mechanical properties were systematically investigated. The results indicated that SFPB treatment can form a gradient nanostructure on the surface of the lightweight Fe–28Mn–8Al–1C steel. With a gas pressure of 1.0 MPa and an impact time of 60 s, the surface roughness was minimized, and the corresponding strength parameters reached their highest values. With increases in the impact time and gas pressure, the grain size of the surface nanocrystalline layer gradually decreased, whereas the surface microhardness and the depth of the severe plastic deformation layer increased. However, excessively long impact time or excessively high gas pressure led to the formation of microcracks, resulting in a decrease in the strength. After SFPB treatment, lightweight Fe–28Mn–8Al–1C steel still exhibited good plasticity with elongation above 46 %, but the tensile fracture morphology changed from ductile fracture (before SFPB) to mixed ductile and brittle fracture (after SFPB).